2020
DOI: 10.31235/osf.io/z3v2h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptation and resilience of commercial fishers in the Northeastern United States during the early stages of the COVID-19 pandemic

Abstract: Commercial fisheries globally experienced numerous and significant perturbations during the early months of the COVID-19 pandemic, affecting the livelihoods of millions of fishers worldwide. In the Northeastern United States, fishers grappled with low prices and disruptions to export and domestic markets, leaving many tied to the dock, while others found ways to adapt to the changing circumstances brought about by the pandemic. This paper investigates the short-term impacts of the early months of the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Some stocks had landings in line with previous years, including those most familiar to US consumers, for example haddock ( Melanogrammus aeglefinus, Gadidae). Conversely, stocks targeted for exporting, for example monkfish ( Lophius americanus, Lophiidae), experienced declines in both landings and price (Smith et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some stocks had landings in line with previous years, including those most familiar to US consumers, for example haddock ( Melanogrammus aeglefinus, Gadidae). Conversely, stocks targeted for exporting, for example monkfish ( Lophius americanus, Lophiidae), experienced declines in both landings and price (Smith et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Fisheries like those in Alaska point to examples where weekly updates of publicly available landings data can help inform science and policy. Although surveys of seafood workers were deployed during the pandemic (van Senten et al., 2020; Smith et al., 2020; Stoll et al., 2020), these were often unplanned and lacked pre‐pandemic baselines. These types of surveys should be a more regular component of government agencies in order to capture the full social and economic effects of shocks.…”
Section: Discussionmentioning
confidence: 99%
“…ASNs exist worldwide and were identified as a "bright spot" in both high-and low-income countries during the early months of the COVID-19 pandemic (Bennett et al, 2020;Gephart et al, 2020;Loring et al, 2020;OMalley, 2020). For example, in the northeast, United States, Smith et al (Smith et al, 2020) found that 60% of the 258 fishers they surveyed reported adapting to local and direct seafood sales during the pandemic. Similarly, in a global survey of more than 150 fishing organizations from 21 countries, Pita et al (2020) found that 48% of respondents had shifted to direct to consumer sales through ASNs.…”
Section: Alternative Seafood Network As a Source Of Systemic Resiliencementioning
confidence: 99%
“…The seafood industry has been a case-in-point for the impacts of the pandemic on society: globally, the industry has experienced significant disruptions, including small-scale fisheries (SSF), because of how closely actors in the value chain must work together (FAO, 2020a;Bennett et al, 2020;Tester, 2020). However, some in the seafood industry are finding resilience and new venues for success through community-based and other alternative marketing operations (Smith et al, 2020;Love et al, 2021;Stoll et al, 2021).…”
Section: Introductionmentioning
confidence: 99%